Proceedings of USM-AUT International Conference 2012 Sustainable Economic Development: Policies and Strategies - Hooi, Hooi Lean (School of Social Sciences, Universiti Sains Malaysia, 2012)
This proceedings includes papers presented at the USM-AUT International Conference (UAIC 2012) carrying the theme “Sustainable Economic Development: Policies and Strategies”, held on 17-18 November 2012 at Bayview Beach Resort Penang Malaysia. This conference is jointly organized by the School of Social Sciences, Universiti Sains Malaysia (USM), Malaysia, and Faculty of Business and Law, Auckland University of Technology (AUT), New Zealand. We received a total of 167 papers from various institutions and organizations around the world where 82 papers were accepted for inclusion in this proceedings. The proceedings is compiled according to the three sub themes of the conference. It covers both theoretical and empirical works from the scholars globally. It is hoped that the collection of these conference papers will become a valuable reference to the conference participants, researchers, scholars, students, businesses and policy makers. The proceedings will be submitted to Thomson ISI for indexing.